Chemical Composition and Antioxidants of Lepidium Sativum and L. aucheri - Ola Adel Al-Saad; Sahar A. A. Malik Al-Saadi (University of Thi-Qar Journal of Science, 2021)
Antioxidant activity of total glucosides contents of the extract of Lepidium sativum and Lepidium aucheri leaves was determined using free radical scavenging activity 2,2-Diphenyl-1-Picrylhydrazyle (DPPH) by adding different concentrations of glycoside to DPPH. The inhibitory activity determined by using five different concentrations of glycolysis of L. sativum and L. aucheri leaves extracts. The results indicated that 1000 mg/ ml concentration showed radical scavenging activity as strong as than low concentrations. Out of the two species L. aucheri had the greatest abundance of antioxidant compared with L. sativum. The inhibition percentage of L. sativum as found to be 78.211 in 1000 μg/mL, was comparatively lower than of standard ascorbic acid and L. aucheri extract 91.972 and 97.018 μg/mL, respectively. L. aucheri extract has strong activity that reach almost as high as ascorbic acid. Total antioxidant capacity of the test samples was calculated using the standard line as ascorbic acid equivalents (AAE) per gram of the leaves extract, of ascorbic acid (y = 0.0629x + 48.356, R² = 0.4085). The results of L. sativum and L. aucheri was (y = 0.0436x + 43.48, R² = 0.3493) and (0.0648x + 48.761, R² = 0.3483) respectively. The two species with various concentration showed the strongest antioxidant activity with its significantly smaller IC50 values,the best exhibited a quite recorded in L. aucheri (IC50 =19.12 μg/ mL, followed by L. astivum 149.541 μg/mL. compared with ascorbic acid 26.136 μg/ mL. The GC analysis indicated that L. sativum had high number of glycoside compounds 36 components compared with L. aucheri 19 components. The major components of L. sativum were found to be: Benzyl nitrile (22.24 %), N,N-Dimethylaminoethanol (17.53%), 2-Hydroxy-1-(1’-pyrrolidiyl)-1-buten-3-one (11.08 %), D-Proline (7.33 %), Butyrolactone (4.97%) and 1-(1’-pyrrolidinyl)-2-propanone (4.14), GC -MS analysis of L. aucheri represented DL-Proline, 5-oxo-, methyl ester (42.26%); 2-Furancarboxaldehyde, 5-methyl- (12.64%); 4H-Pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl- (9.87%); Hexadecanoic acid, 2-hydroxy-1-(hydroxymethyl)ethyl ester (2.33%); 2-Methoxy-4-vinylphenol (2.02%).